Community Responses to Flooding in Tanjung Pura District, North Sumatra: A Qur'anic Perspective on Surah Ar-Rum (30:41) - Siti Khoiriah Harahap; M. Jamil (Kartika: Jurnal Studi Keislaman, 2026)
Flooding that struck Tanjung Pura District, North Sumatra, at the end of 2025 resulted from the interaction between hydrometeorological factors and environmental degradation caused by human activities. This study aims to analyze the responses of flood-affected communities and examine the relevance of Surah Ar-Rum (30:41) as a foundation for psychoecological healing and the development of ecological awareness from an Islamic perspective. The study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with flood-affected residents and analyzed thematically, followed by interpretative analysis using Tafsir al-Misbah, Tafsir al-Azhar, and Tafsir an-Nur. The findings reveal that community responses evolved from panic and anxiety toward stronger social solidarity, enhanced spirituality, and greater ecological awareness. The interpretation of Surah Ar-Rum (30:41) emphasizes that environmental degradation caused by human actions serves as a divine reminder for humanity to restore harmonious relationships with God, fellow human beings, and nature. These findings demonstrate that Qur'anic values provide a conceptual foundation for psychoecological healing while fostering sustainable ecological awareness among disaster-affected communities